(untitled) (قضايا سياسية, 2025)
The research dealt with the phenomenon of military coups in the countries of the African continent by studying their causes and mechanisms for returning to constitutional legitimacy after the coups occurred, which led to a state of political instability and obstructed the process of democratic transformation in some countries. The research focused on three African models: Nigeria, which was able to achieve a degree of trust between the rulers and the ruled after decades of fighting and rivalry caused by conflicts and coups, by paying attention to establishing constitutional frameworks that regulate the relationship between power and the people, and discussed the experience of Niger, being the country that witnessed the last military coups in Africa in 2023 and was unable to build a constitutional authority until today, in addition to the Mauritanian model, which witnessed a keenness on mechanisms to strengthen the constitutionality of authority by convincing the warring parties to follow political action as an alternative to violence. The study of military coups in Africa shows that the military institution may be the most common means of bringing about unconstitutional political change, which prompts countries witnessing coups to search for mechanisms to return to constitutional legitimacy.